Electrical latency predicts the optimal left ventricular endocardial pacing site: results from a multicentre international registry. Issue 12 (23rd April 2018) - Sieniewicz, Benjamin J; Behar, Jonathan M; Sohal, Manav; Gould, Justin; Claridge, Simon; Porter, Bradley; Niederer, Steve; Gamble, James H P; Betts, Tim R; Jais, Pierre; Derval, Nicolas; Spragg, David D; et al.
Abstract: Aims: The optimal site for biventricular endocardial (BIVENDO ) pacing remains undefined. Acute haemodynamic response (AHR) is reproducible marker of left ventricular (LV) contractility, best expressed as the change in the maximum rate of LV pressure (LV-d p /d t max ), from a baseline state. We examined the relationship between factors known to impact LV contractility, whilst delivering BIVENDO pacing at a variety of LV endocardial (LVENDO ) locations. Methods and results: We compiled a registry of acute LVENDO pacing studies from five international centres: Johns Hopkins-USA, Bordeaux-France, Eindhoven-The Netherlands, Oxford-United Kingdom, and Guys and St Thomas' NHS Foundation Trust, London-UK. In all, 104 patients incorporating 687 endocardial and 93 epicardial pacing locations were studied. Mean age was 66 ± 11 years, mean left ventricular ejection fraction 24.6 ± 7.7% and mean QRS duration of 163 ± 30 ms. In all, 50% were ischaemic [ischaemic cardiomyopathy (ICM)]. Scarred segments were associated with worse haemodynamics (d p /d t max ; 890 mmHg/s vs. 982 mmHg/s, P < 0.01). Delivering BiVENDO pacing in areas of electrical latency was associated with greater improvements in AHR ( P < 0.01). Stimulating late activating tissue (LVLED >50%) achieved greater increases in AHR than non-late activating tissue (LVLED < 50%) (8.6 ± 9.6% vs. 16.1 ± 16.2%, P = 0.002). However, the LVENDO pacing location with the latest Q-LV, was associated with the optimal AHR in just 62% of cases. Conclusions: Identifying viable LVENDO tissue which displays late electrical activation is crucial to identifying the optimal BiVENDO pacing site. Stimulating late activating tissue (LVLED >50%) yields greater improvements in AHR however, the optimal location is frequently not the site of latest activation.